Thrombectomy in patients with basilar artery thrombosis - G. R. Ramazanov; E. A. Kovaleva; E. V. Klychnikova; L. S. Kokov; H. V. Korigova; R. Sh. Muslimov; M. V. Parkhomenko; S. S. Petrikov; V. N. Stepanov (Неотложная медицинская помощь)
Introduction. This article is devoted to the discussion of a life-threatening condition - basilar artery thrombosis (BAT). The article presents the results of a comparative analysis of two groups of patients with angiographically confirmed BAT: with and without reperfusion therapy.Relevance. Basilar artery thrombosis is a life-threatening condition in which mortality can reach 95%, and severe neurological deficits and dependence in everyday life on others (modified Ran-kin Scale (mRS), score 4–5) are observed in 65% of surviving patients. Ischemic stroke (IS) due to BAT is diagnosed in 1–4% of patients with acute cerebrovascular event (ACVE). Currently, reperfusion therapy (RT) in the form of systemic thrombolytic therapy (sTLT) with rt-PA and/or thrombectomy (TE) is the only effective and safe method for treating patients with IS. In randomized trials, it was found that RT, whether it is sTLT, TE or a combination of these techniques, despite the best degree of functional recovery in patients by day 90 from the onset of the disease, does not lead to a statistically significant decrease in mortality. Nevertheless, the results of 10 prospective studies of the use of endovascular treatment in patients with IS in the posterior circulation system indicate that this type of therapy leads to a decrease in 90-day mortality from 95% to 16–47% in case of successful recanalization (mTICI (modified Thrombolysis in Cerebral Infarction), 2–b–3).Aim of study. To assess the safety and efficacy of TE in patients with BAT.Material and methods. This study included 15 patients with IS, admitted within the 6-hour therapeutic window, and confirmed BAT by CT and/or MRangiography. The baseline level of wakefulness was assessed using the Glasgow Coma Scale (GCS), and the severity of neurological deficit was assessed by the National Institutes of Health Stroke Scale (NIHSS).Results. Basilar artery thrombectomy was performed in 7 patients (endovascular treatment group), 8 patients received no endovascular treatment (standard therapy group). Good clinical outcomes by day 90 from the onset of the disease (mRS, score 0–2) were observed in 57.1% of patients in the endovascular treatment group and in 12.5% of patients in the standard therapy group. However, these differences were not statistically significant (p>0.05). There were also no differences between the two groups in functional outcomes and Rivermead mobility index (RMI) by day 90 from the onset of the disease (Barthel Index of Activities of Daily Living (BI) score 97±5.0 and 100, RMI score 14.0±0.0 and 15 in the endovascular treatment group and standard therapy group, respectively). Mortality by day 90 in the endovascular treatment group was 42.9% (3 patients), in the standard therapy group — 87.5% (7 patients). In the subgroup of patients with GCS score at admission no more than score 8, there was a statistically significant strong two-way negative correlation between TE performance and mortality (r=-1.0; p=0.000), as well as a positive correlation between TE and a Rankine score by day 90 (r=0.956; p=0.003). Mortality was statistically significantly lower in the endovascular treatment group compared to the standard therapy group (0% versus 100%, respectively, p=0.025). Clinical outcomes of the disease by day 90 were statistically significantly better in the endovascular treatment group: mRS, score 0–2 in 100% of cases versus 0% in the standard treatment group (p=0.028).Conclusion. Currently, the only effective treatment for basilar artery thrombosis is thrombectomy. The possibility of performing thromboectomy in these cases should be considered in all patients, regardless of the severity of the stroke and the decrease in the level of wakefulness, since endovascular treatment in this case is a life-saving procedure. The symptom of a hyperdense basilar artery can be used as a diagnostic tool for suspected basilar artery thrombosis, but should not rule out angiography. In our series of observations, the mortality rate in patients who underwent thrombectomy was 42.9%. Good functional outcomes (mRS, score 0–2) and the absence mobility limitation (RMI, score 14) were observed in 57.1% of patients by day 90 after thrombectomy.